2007
DOI: 10.1002/prot.21361
|View full text |Cite
|
Sign up to set email alerts
|

Solution structures, dynamics, and lipid‐binding of the sterile α‐motif domain of the deleted in liver cancer 2

Abstract: The deleted in liver cancer 2 (DLC2) is a tumor suppressor gene, frequently found to be underexpressed in hepatocellular carcinoma. DLC2 is a multidomain protein containing a sterile alpha-motif (SAM) domain, a GTPase-activating protein (GAP) domain, and a lipid-binding StAR-related lipid-transfer (START) domain. The SAM domain of DLC2, DLC2-SAM, exhibits a low level of sequence homology (15-30%) with other SAM domains, and appears to be the prototype of a new subfamily of SAM domains found in DLC2-related pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 50 publications
(82 reference statements)
1
27
0
Order By: Relevance
“…The SAM domain was thought to act as a protein interaction module through the formation of homo-and hetero-oligomers with other SAM domains, or even RNA and DNA (26). Results of structural studies of the DLC2 SAM domain have shown that it may also bind lipids (27).…”
Section: Typical Dlc Protein Possesses Three Domains: Sam Rhogap Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAM domain was thought to act as a protein interaction module through the formation of homo-and hetero-oligomers with other SAM domains, or even RNA and DNA (26). Results of structural studies of the DLC2 SAM domain have shown that it may also bind lipids (27).…”
Section: Typical Dlc Protein Possesses Three Domains: Sam Rhogap Andmentioning
confidence: 99%
“…As key regulators of diverse cellular pathways GTPases affect such crucial processes as transcriptional regulation, cell cycle progression, apoptosis, and membrane trafficking (1,2). This family of small (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) signaling G proteins (guanine nucleotide-binding proteins) constitutes a major branch of the Ras superfamily (3). Membership in the superfamily of Ras proteins is determined by the presence of the GTPase domain.…”
Section: Introductionmentioning
confidence: 99%
“…The three DLC proteins are characterized by the presence of three motifs: a sterile α motif (SAM), a RhoGAP catalytic domain, and a START (Star-related lipid transfer) domain (18). The SAM domain consists of approximately 70 residues and has been shown to play several roles particularly as protein interaction modules because of its ability to interact with other SAM domains (19). SAM domains are located on the N-terminus and may bind to DNA or RNA (20).…”
Section: Introductionmentioning
confidence: 99%
“…SAM domains are located on the N-terminus and may bind to DNA or RNA (20). DLC2-SAM shows only 15-30% homology with other SAM domains and is considered as the prototype in the family of the DLC2-related proteins (19). When searching for additional candidate tumor suppressor loci critical in hepatocellular carcinoma after the well-known and established tumor suppressor genes p53, c-myc, p16 ink4 and β-catenin, Ching et al identified a novel gene DLC2 on chromosome 13q12 which was found to be underexpressed in hepatocellular carcinoma (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…The ϳ70-amino acid SAM domains are found in over 200 human proteins and are known to serve as protein-protein interaction domains (14). However, the recent structural determinations of the DLC-2 SAM domain suggest that this SAM domain is structurally distinct and hence may be functionally distinct from canonical SAM domains (15,16). The RhoGAP domain of DLC-1 has been shown to stimulate RhoA inactivation in vitro and in vivo (5,17).…”
mentioning
confidence: 99%